2018
DOI: 10.1140/epjb/e2017-80485-8
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of organ pipes

Abstract: We investigate synchronization of coupled organ pipes. Synchronization and reflection in the organ lead to undesired weakening of the sound in special cases. Recent experiments have shown that sound interaction is highly complex and nonlinear, however, we show that two delay-coupled Van-der-Pol oscillators appear to be a good model for the occurring dynamical phenomena. Here the coupling is realized as distance-dependent, or time-delayed, equivalently. Analytically, we investigate the synchronization frequency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…By contrast, synchronization is also used to explain brain processes serving the development of syntax and its perception (Koelsch et al, 2013;Large et al, 2015;Bader, 2020). Generally, synchronization theory is of great importance for the analysis and understanding of musical acoustics and music psychology (Bader, 2013;Sawicki et al, 2018a;Hou et al, 2020;Shainline, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, synchronization is also used to explain brain processes serving the development of syntax and its perception (Koelsch et al, 2013;Large et al, 2015;Bader, 2020). Generally, synchronization theory is of great importance for the analysis and understanding of musical acoustics and music psychology (Bader, 2013;Sawicki et al, 2018a;Hou et al, 2020;Shainline, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the notion of relay synchronization has been extended from completely synchronized states to partial synchronization patterns in the individual layers of a three-layer multiplex network. It has been shown that the three-layer structure of the network allows for (partial) synchronization of chimera states in the outer layers via the relay layer [27][28][29][30][31]. Going towards more realistic models, time-delay plays an important role in the modeling of the dynamics of complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, synchronization is also used to explain brain processes which subserve for development of syntax and its perception (Koelsch et al, 2013;Large et al, 2015;Bader, 2020). In general, synchronization theory is highly important to analyze and understand musical acoustics and music psychology (Joris, 1994;Bader, 2013;Sawicki et al, 2018a;Hou et al, 2020;Shainline, 2020). While the neurophysiological processes when listening to music remain ongoing research, it is presumed that a certain degree of synchrony can be observed while listening to music and building up expectations.…”
Section: Introductionmentioning
confidence: 99%